Correlation of TED Laterality with Thyroid Status among Thyroid Eye Disease (TED) Patients in a Tertiary Hospital in Indonesia - Lutfiyah, Zahirah Siti; Lutfi, Delfitri; Susanto, Hermawan; Sutjipto (Current Internal Medicine Research and Practice Surabaya Journal, 2024)
Introduction: Thyroid eye disease (TED), an autoimmune thyroid disorder, is prevalent in Asian countries and exhibits a variety of manifestations. Orbital involvement in TED is usually bilateral but may occur unilaterally in some cases. While it is commonly associated with hyperthyroidism, it also manifests in individuals with hypothyroidism or euthyroidism. The purpose of this study was to investigate the relationship between TED laterality and thyroid status in TED patients treated at the Eye Oncology Clinic of Dr. Soetomo General Academic Hospital in Surabaya, Indonesia.Methods: The study was retrospective, analytical and observational. Patients diagnosed with TED who were treated at Dr. Soetomo General Academic Hospital between January 2019 and December 2021 were the focus of this study. SPSS analyses of medical records that satisfied the sample criteria were used to compile the data for this study.Results: There were 88 samples that were dominated by females (57.95%) and aged 41 – 50 (32.96%). Proptosis was the most common clinical manifestation (94.32%), with compressive optic neuropathy was the least common (3,41%). Eyelid retraction occurred in only 22.7% of the patients. TED was categorized into unilateral (44.32%) and bilateral (50%). The majority had hyperthyroidism (70.45%), followed by euthyroidism (25%), and hypothyroidism (4.55%). It was found that there was a significant correlation between thyroid status and TED laterality. Compared to euthyroidism, abnormal thyroid conditions such as hyperthyroidism and hypothyroidism develop bilateral TED more frequently than normal thyroid conditions.Conclusion: There was a correlation between TED laterality and thyroid status among patient TED.